Stress–dilatancy behavior for sand under loading and unloading conditions. (16th December 2011) - Yin, Zhen‐Yu; Chang, Ching S.
SUMMARY Experimental results have shown very different stress–dilatancy behavior for sand under loading and unloading conditions. Experimental results have also shown significant effects of inherent anisotropy. In this article, a micromechanics‐based method is presented, by which the stress–dilatancy relation is obtained through the consideration of slips at the interparticle contacts in all orientations. The method also accounts for the effect of inherent anisotropy in sand. Experimental results on Toyoura sand and Hostun sand are used for illustration of the proposed method. Copyright © 2011 John Wiley & Sons, Ltd.